Sustainable supply chain evaluation: A dynamic double frontier network DEA model with interval type-2 fuzzy data - Zhou, Xiaoyang; Wang, Ying; Chai, Jian; Wang, Liqin; Wang, Shouyang; Lev, Benjamin (Information sciences, 2019)
Accompanying with strengthening consciousness of environmental protection and social security, developing sustainable supply chain (SSC) has been becoming more and more important. Under this background, it is essential to deeply understand and evaluate SSCs from comprehensive economy-environment-society aspects. In order to do this, this paper considers the SSC as a dynamic three-stage network system consisting of supplier, manufacturer and distributor across multiple periods, and establishes a novel dynamic network DEA model with desirable and undesirable indicators to compute the detailed efficiencies based on both effective and invalid production frontiers. In the model, the degrees of environmental pollution and customer satisfaction are described as interval type-2 fuzzy sets. Then a method considering the optimistic-pessimistic attitude of decision makers is introduced to get solutions. For case study, the proposed DEA model is used to evaluate 20 SSCs, and analysis from time and stage perspectives are conducted to show the detailed performance. According to the results, the evaluated SSCs can be divided into four groups with different patterns, the weakness stage and period for each SSC can also be identified. The comparison and sensitivity analysis demonstrates our proposed model has more discriminating power and the ability of providing more managerial insights. Not only the sensitivity degree of a SSC to the attitude change of decision makers can be determined, but also the important indicator in different aspects for each SSC can be pointed out.